Assessing the Tax Amnesty Program in Indonesia Through System Success and Trust Models - Muji, Muji; Maupa, Haris; Cokki, Cokki (Malikussaleh University, Aceh, Indonesia, 2025)
The success of a Tax Amnesty Program (TAP) in developing countries such as Indonesia depends not only on fiscal policy execution but also on how taxpayers perceive and trust the program. This study integrates the Information System Success Model with the trust construct to empirically examine the factors affecting TAP performance from a citizen-centric perspective. Using a quantitative approach, the research involved 414 Indonesian taxpayers selected through stratified random sampling, with data analysed using SmartPLS 3.0. One hundred eighty-seven valid responses were retained after a filtering process based on TAP knowledge awareness. The proposed model includes six constructs: Information Quality (INQ), Program Quality (PGQ), Service Quality (SVQ), Taxpayer Trust (TPT), Taxpayer Satisfaction (TSF), and Net Benefits (NBF). The structural model revealed that INQ significantly affects both TPT and TSF, and that TSF has the most decisive influence on NBF. However, PGQ and SVQ did not considerably impact TPT, suggesting that trust in TAP may be influenced more by institutional and cultural factors than perceived technical features. The findings highlight the necessity to enhance tax information accuracy and transparency while strengthening public trust and satisfaction. This study provides an integrative model to evaluate TAP success and offers practical insights for policymakers aiming to improve taxpayer participation through trust-based interventions. The novelty lies in quantitatively integrating information systems and behavioural trust constructs within the tax amnesty framework.